Principals' acceptance of school improvement partners mentoring practice in Malaysia - Padzil, Iskandar; Abdul Kadir, Suhaida; Mohd Ayub, Ahmad Fauzi; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2019)
The purpose of this paper is to explore the principals’ acceptance of School Improvement Partners (SIPartners+) mentoring practice in selected secondary schools in East Malaysia. The case study of four principals in low-performance school was qualitative and interpretive. This paper shows that mentoring practice was still less acceptable by the school principals as they felt that SIPartners+ as an outsider who intervene the school management. The findings dereived from four research questions which related to the needs of mentoring, SIPartners+ competency, SIPartners+ knowledge and SIPartners+ experience. These findings were limited to the sample of principals used for this analysis. Researchers are encouraged to examine SIPartners+ mentoring in other contexts. The results of this research suggested for the practitioners to reflect on their roles in education collaboratively and call for further research on SIPartners+ practices between urban and rural schools. This paper is one of the few documents that studies mentoring in the Malaysian education system. It forms a basis for future empirical research in this area.